Reconstruction after periacetabular tumor resection with Lumic (R) endoprosthesis: What are the midterm results? - EROL, BÜLENT; ŞİRİN, EVRİM (WILEY, 2021)
Introduction This study aimed to analyze the midterm outcomes of LUMiC (R) endoprosthetic reconstruction following periacetabular resection of primary bone sarcomas and carcinoma metastases. Patients and Methods We retrospectively reviewed the charts of 21 patients (11 male [52.3%], 10 female [47.6%]; mean age 47 +/- 16 years) for whom a LUMiC (R) endoprosthesis (Implantcast) was used to reconstruct a periacetabular defect after internal hemipelvectomy. The tumor was pathologically diagnosed as Ewing's sarcoma in six (28.5%), chondrosarcoma in 10 (47.6%), and bone metastasis from carcinoma in five (23.8%) patients. Results The median follow-up of patients was 57.8 months (95% confidence interval: 51.9-63.7). The implant survival rate at 1, 2, and 5 years were 95.2%, 85.7%, and 80.9%, respectively. The overall complication rate was 33.3% (n = 7). Four (19%) complications resulted in reconstruction failure. Total reoperation rate was 28.5% (n = 6). The causes of failure were soft tissue failure/dislocation in two patients, aseptic loosening in one, infection in two, and local recurrence in two. At the time of study, seven patients were alive with no evidence of disease, seven were alive with disease, and seven died of disease. The 5-year overall survival rate and local recurrence-free survival rates were 67% and 76%, respectively. The median Musculoskeletal Tumor Society score at final follow-up was 70% (range: 50%-86.6%). Conclusion We conclude that LUMiC (R) endoprosthesis provides good functional outcomes and a durable reconstruct. Even though this reconstruction method presents some complications, it provides a stable pelvis in the management of periacetabular malignant tumors.
Keywords: endoprosthetic reconstruction; LUMiC® endoprosthesis; metastasis; periacetabular tumor; sarcoma; HEMIPELVIC PROSTHESIS; PELVIC RECONSTRUCTION; SADDLE PROSTHESIS; CLASSIFICATION; SARCOMA